Analysis of the Conflict Resolution Technologies Training Impact in the Sphere of Local Self-Government on the Formation of Conflict Resolution Competency - A. Maslikov, A.; N. Ostrovskii, A.; O.Sulyagina, Ju. (International Journal of Engineering and Technology, 2018)
The article is devoted to demonstrating the adaptation of the most effective forms of social interaction associated with the practice of resolving social conflicts. Such forms of conflict resolution were taken by authors from the description of the stable interaction of the Russian community in the nineteenth and early twentieth centuries. There is a methodology of â€œVillage meetingâ€ (â€œSelâ€™skij skhodâ€ in rus.) based on the analysis of the main points focused on the conflict resolution of the Russian community. The main task of the training is to realize the importance of using traditional socio-cultural technologies with a high degree of efficiency. The authors have received an answer to the question of the influence of training in conflict management technologies on the sphere of local self-government with the formation of conflictological competencies in resolving social conflicts based on the traditional Russian practices of self-government and its reconciliation, â€œVillage meetingâ€ (â€œSelâ€™skij skhodâ€). Approbation of results of the methodology allows to detect number of significant qualities, such as solidarity, unity, penitence, collective responsibility, and the ability to adequately assess the various forms of relationships.Â Â